Epilepsy is associated with ventricular alterations following convulsive status epilepticus in children. Issue 4 (21st August 2017) - Ali, Wail; Bubolz, Beth A.; Nguyen, Linh; Castro, Danny; Coss‐Bu, Jorge; Quach, Michael M.; Kennedy, Curtis E.; Anderson, Anne E.; Lai, Yi‐Chen
Summary: Objective: Convulsive status epilepticus can exert profound cardiovascular effects in adults, including ventricular depolarization–repolarization abnormalities. Whether status epilepticus adversely affects ventricular electrical properties in children is less understood. Therefore, we sought to characterize ventricular alterations and the associated clinical factors in children following convulsive status epilepticus. Methods: We conducted a 2‐year retrospective case–control study. Children between 1 month and 21 years of age were included if they were admitted to the pediatric intensive care unit with primary diagnosis of convulsive status epilepticus and had 12‐lead electrocardiogram (ECG) within 24 h of admission. Children with heart disease or ion channelopathy, or who were on vasoactive medications were excluded. Age‐matched control subjects had no history of seizures or epilepsy. The primary outcome was ventricular abnormalities represented by ST segment changes, abnormal T wave, QRS axis deviation, and corrected QT (QTc) interval prolongation. The secondary outcomes included QT/RR relationship, beat‐to‐beat QTc interval variability, ECG interval measurement between groups, and clinical factors associated with ECG abnormalities. Results: Of 317 eligible children, 59 met the inclusion criteria. History of epilepsy was present in 31 children (epileptic) and absent in 28 children (nonepileptic). Compared with the control subjects (n = 31), the status epilepticus groups were more likely to have an abnormal ECG, with overall odds ratios of 3.8 and 7.0 for the nonepileptic and the epileptic groups, respectively. Simple linear regression analysis demonstrated that children with epilepsy exhibited impaired dependence and adaptation of the QT interval on heart rate. Beat‐to‐beat QTc interval variability, a marker of ventricular repolarization instability, was increased in children with epilepsy. Significance: Convulsive status epilepticus can adversely affect ventricular electrical properties and stability in children, especially those with epilepsy. These findings suggest that children with epilepsy may be particularly vulnerable to seizure‐induced arrhythmias. Therefore, postictal cardiac surveillance may be warranted in this population.